"Turnpike" Theory With (Under) Consumption - Rader, Trout (Review of Economic Studies, 1975)
Journal Article ”Turnpike“ Theory With (Under) Consumption Get access Trout Rader Trout Rader Washington University, St Louis Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 42, Issue 1, January 1975, Pages 155–165, https://doi.org/10.2307/2296829 Published: 01 January 1975